Impact of Probiotic B. infantis EVC001 Feeding in Premature Infants on the Gut Microbiome, Nosocomially Acquired Antibiotic Resistance, and Enteric Inflammation - Nguyen, Marielle; Holdbrooks, Heaven; Mishra, Prasanthi; Abrantes, Maria A.; Eskew, Sherri; Garma, Mariajamiela; Oca, Cyr-Geraurd; McGuckin, Carrie; Hein, Cynthia B.; Mitchell, Ryan D.; Kazi, Sufyan; Chew, Stephanie; et al. (Frontiers in Pediatrics, 2021)
Background: Preterm birth is a major determinant of neonatal survival and morbidity, but the gut microbiome and associated enteric inflammation are also key factors in neonatal development and the risk of associated morbidities. We prospectively and longitudinally followed two cohorts of preterm infants, one of which was fed Bifidobacterium longum subsp. infantis (B. infantis) EVC001 daily, and the other was not fed a probiotic. Hospital feeding protocol assigned all infants born at less than 1500g and/or 34 weeks corrected gestational age to the probiotic feeding protocol, whereas infants born at > 1500g and/or 34 weeks corrected gestational age were not fed a probiotic. Fecal samples collected opportunistically (approximately 2 samples per week) throughout the hospital stay were analyzed from 292 samples collected from 77 infants. Fecal samples were subjected to shotgun metagenomic sequencing and quantification of enteric inflammation markers. We also collected de-identified metadata from patient medical records. Results: The gut microbiome of preterm infants was typified by a high abundance of Enterobacteriaceae and/or Staphylococcaceae and multivariate modeling identified the probiotic intervention, rather than degree of prematurity, day of life, or other clinical interventions as the primary source of change in the gut microbiome. Among infants fed B. infantis EVC001, a high abundance of total Bifidobacteriaceae developed rapidly, the majority of which was B. infantis confirmed via subspecies-specific qPCR. Associated with this higher abundance of Bifidobacteriaceae, we found increased functional capacity for utilization of human milk oligosaccharides (HMOs), as well as reduced abundance of antibiotic resistance genes (ARGs) and the taxa that harbored them. Importantly, we found that infants fed B. infantis EVC001 experienced diminished enteric inflammation, even when other clinical variables were accounted for using multivariate modeling. Conclusion: These results provide an important observational background for probiotic use in a NICU setting, and describe the clinical, physiological, and microbiome-associated improvements in preterm infants associated with B. infantis EVC001 feeding.